Immunity to error through misidentification in observer memories: A moderate separatist account. - Perrin, Denis; McCarroll, Christopher Jude (Philosophy & Phenomenological Research, 2023)
Judgments based on episodic memory are often thought to be immune to errors of misidentification (IEM). Yet there is a certain category of episodic memories, viz. observer memories, that seems to threaten IEM. In the resulting debate, some say that observer memories are a threat to the IEM enjoyed by episodic memory (Michaelian, 2021); others say that they pose no such threat (Fernández, 2021; Lin, 2020). In this paper, we argue for a middle way. First, we frame the debate, claiming that the existing literature lacks a satisfying definition both of observer memories and of the precise issue of errors of identification in such memories. Then, we contribute to the debate by challenging an anti‐separatist view about the relation between phenomenal and intentional features of observer memories that looms behind this debate. On this view, if the rememberer's self is a phenomenal feature of the memory, by implication it is also built into the intentional content. We reject this view and offer a moderate separatist account. Distinguishing between empirically‐grounded species of observer memories, we say that the phenomenal self sometimes is, and sometimes is not built into the intentional content of the memory, and this results in different implications for IEM.